Integrated Management of Food Security and National Defense Systems to Face Global Challenges - Yudianto Putrajaya; Setyo Riyanto; Dewi Nusraningrum; Mafizatun Nurhayati; Guntur Eko Saputro (Journal of Social Work and Science Education, 2026)
The integration of food security with the national defense system faces significant challenges in the ever-changing global dynamics. Food crises triggered by climate change, geopolitical conflicts, and dependence on food imports pose serious threats to national sovereignty. From a management perspective, this integration requires a comprehensive and sustainable management strategy. One of the main challenges is the high dependence on food imports, which creates vulnerability to global supply disruptions. Therefore, integrated management is needed that emphasizes efficiency, cross-sector coordination, and strengthening local capacity in food provision. The purpose of this study is to analyze the relationship between food security and the national defense system within the framework of strategic management in facing global challenges, such as climate change, dependence on food imports, and potential threats of economic and geopolitical crises. The theory used is Food System Theory, which views food as an interconnected system ranging from production, distribution, to consumption. The research method used is a literature study with a managerial approach, namely reviewing, analyzing, and synthesizing various relevant literature sources. The results of the study indicate several important indicators in the management of the integration of food security and national defense, including: Local Food Availability Management, strengthening domestic production. Defense and Food Security Policy, integration of cross-sector policies. Import Dependency Risk Management, reducing vulnerability to global supply. Utilization of Technology and Innovation, increasing production and distribution efficiency. Inter-Agency Collaborative Management, strengthening synergy between government, communities, and the private sector.